Metal Composites Behaviour Under Biaxial Stresses - J. Jai; M.N. Berhan (ASEAN Journal on Science and Technology for Development, 2006)
For this study, different volume fraction (vol.%) of particulate alumina (Al2O3)reinforced aluminium alloy (Al 6061) with 5 vol.%, 15 vol.% and 25 vol.% are produced by powder metallurgy method. These samples were subjected to biaxial stresses in order to investigate the behaviour of the metal matrix composites (MMCs). Microstructure analysis on the individual sample before and after loading was performed under scanning electron microscopy. The small particles of 2 µm in size have exhibited strong interfacial bonding with the matrix. The particles of 5 µm in size have shown fractures and debonding interface. Large particles of above 20 µm in size have revealed severe fractures and particles pulled out. Behavior of the MMC was explained by relating the microstructures and displacement directions of the undeformed and deformed samples. Some understandings on the behaviour of the MMCs with different vol.% of Al2O3 due to biaxial stresses have been established.